Assessing the Impact of Social Media Marketing Factors on Restaurant Customers’ Purchase Intentions in Negeri Sembilan, Malaysia - Khairun Nuha Roslin; Nur Farah Adibah Binti Iman; Nik Mohamad Zulfadli Nik Mohd Fahmi; Wan Nor Bayah Wan Kamarudin; Muhammad Muzhaffar Mohd Aris (Information Management and Business Review, 2025)
In recent years, digital platforms, particularly social media, have transformed how customers discover and choose dining options. These platforms significantly influence purchase decisions, marking a shift in how businesses in the food and beverage sector engage with their audiences. Hence, this study aims to assess the impact of social media marketing on the purchase intentions of restaurant customers in Negeri Sembilan. It focuses on three key factors, which are menu visuals, advertising, and electronic word-of-mouth (e-WOM). A cross-sectional study has been conducted using purposive sampling, targeting customers with dining experiences at restaurants in Negeri Sembilan who are familiar with social media. A total of 342 usable responses have been collected through an online survey, ready for analysis conducted using SPSS Version 26 to provide meaningful results addressing the research questions of this study. The findings from the hypotheses show that key factors like advertising, menu visuals, and e-WOM have a significant, positive effect on customer purchase intentions. e-WOM and advertising are significant, with e-WOM being the most impactful factor. However, menu visuals have a weaker impact. Descriptively, the respondents have also ranked e-WOM and advertising as their top-priority factors towards their purchase intentions. This study advocates the significance of efficient social media strategies in boosting consumer interactions and influencing buying intentions, offering restaurateurs and marketers insightful information. Hence, expanding the research to include longitudinal studies would provide deeper insights into changing consumer behaviours over time.